Kara Sea freshwater transport through Vilkitsky Strait: Variability, forcing, and further pathways toward the western Arctic Ocean from a model and observations. - Janout, Markus; Hölemann, Jens A; Timokhov, Leonid (PANGAEA, 2019)
Underway (U)CTD data were collected during a 2013 (22. August – 21. September) expedition to the Arctic Ocean aboard the RV Viktor Buinitsky as part of the German-Russian BMBF-funded project Transdrift (The transpolar system of the Arctic Ocean). The UCTD was operated during selected shelf-basin transects as well as to expand the sampling grid on the shelf during transits across the shelf while the ship was transiting with 6 - 11 knots. The UCTD probe records the start time of the measurements and stores 16 samples each second internally. The exact location of each profile was subsequently found based on the time stamp from the cruise track. The unpumped conductivity sensor has a slower response time than the temperature sensor, which makes the computation of salinity from conductivity and temperature potentially spiky, especially in the pycnocline or in frontal regions. We followed the recommendation of the manufacturer to calculate salinity with Seabird processing software. The raw data profiles are provided as well and can be reprocessed if desired. In shallower waters (<200m), the water column was profiled all the way to the seafloor, while in deeper waters, only the upper 200-350m were sampled. Shipboard echo soundings were not available, actual water depths at the profile locations need to be extracted from bathymetric charts (for instance IBCAO ). The UCTD sensors were calibrated before and after the cruise. The upper 3 m of the data were discarded due to the influence of the ship. However, the hull of the ship was shallow and the effect of the ship on mixing surface water properties and disrupting the natural water column structure was relatively small compared with large vessels.
Physical oceanography from underway CTD measurements during the Transdrift 21-expedition to the Laptev Sea in 2013
Keywords: AWI_PhyOce; CTD, underway; CTD-UW; DEPTH, water; Laptev Sea; Laptev Sea System; LSS; Physical Oceanography @ AWI; Pressure, water; Profile; Salinity; System Laptev-Sea: Transdrift; Temperature, water; TRANSDRIFT; Transdrift-XXI; UnderwayCTD (UCTD), Oceanscience; VB13; VB13_10-7a; VB13_10-7b; VB13_10-7c; VB13_10-7d; VB13_10-7e; VB13_10-7g; VB13_10-7h; VB13_10-7i; VB13_10-7j; VB13_10-7k; VB13_10-7l; VB13_10-7m; VB13_10-7n; VB13_10-7o; VB13_10-7p; VB13_10-7q; VB13_10-7r; VB13_10-7s; VB13_10-7t; VB13_10-7u; VB13_10-7v; VB13_10-7w; VB13_10-7x; VB13_10-7y; VB13_10-7z; VB13_10-8a; VB13_10-8b; VB13_10-8c; VB13_10-8d; VB13_10-8e; VB13_10-8g; VB13_10-8h; VB13_10-8i; VB13_13-4a; VB13_13-4b; VB13_13-4c; VB13_13-4d; VB13_13-4e; VB13_13-4f; VB13_13-4g; VB13_13-4h; VB13_13-4i; VB13_13-4j; VB13_13-4k; VB13_13-4l; VB13_13-4n; VB13_15-10a; VB13_15-10b; VB13_15-10c; VB13_15-10d; VB13_15-10e; VB13_15-10f; VB13_15-10g; VB13_15-10h; VB13_15-10i; VB13_15-10j; VB13_15-10k; VB13_15-10l; VB13_15-10m; VB13_15-10n; VB13_15-10o; VB13_15-10p; VB13_15-10q; VB13_15-10r; VB13_15-10s; VB13_15-10t; VB13_15-10u; VB13_15-10v; VB13_15-10w; VB13_15-10x; VB13_15-10y; VB13_15-10z; VB13_15-11a; VB13_15-11b; VB13_15-11c; VB13_15-11d; VB13_15-11e; VB13_15-11f; VB13_15-11g; VB13_15-11h; VB13_15-11i; VB13_15-11j; VB13_15-11k